Fungal sensitization in patients with severe atopic dermatitis as a distinct phenotype - Daria S. Fomina; Marina S. Lebedkina; Anton A. Chernov; Ekaterina A. Nikitina; Olga A. Mukhina; Valeriya I. Mikhaylova (ZAO "Consilium Medicum", 2022)
Background. Many factors influence the development of atopic dermatitis (AD): genetic, environmental (including exposure to allergens), skin barrier damage, and activation of the T2-pathway immune response. Patients with AD, including those with severe disease, are prone to sensitization to various allergens, including fungal ones. Fungal sensitization (FS) promotes autoreactivity to the body's own structures due to shared epitopes with homologous fungal allergens. It can contribute to the development of allergic diseases, including AD, asthma, and rhinitis, as well as to their exacerbation and uncontrolled course. Since FS can be considered a factor aggravating AD, it is relevant to distinguish patients with FS and AD into a separate phenotype. Aim. To characterize the phenotype of patients with severe AD and FS using retrospective data analysis from a digital analytics platform in a real-world clinical setting. Materials and methods. A retrospective observational single-center study was conducted between 01.06.2017 and 01.07.2022. The study cohort included 88 patients with severe AD who were candidates for therapy or received treatment with either dupilumab or upadacitinib. FS was confirmed in 49 patients from the study group. Part of the cohort without FS (n=39) was used as a comparison group. Inclusion criteria: the age over 18 years old; severe AD (SCORAD40 points at the beginning of therapy); determination of specific immunoglobulin E to a panel of fungal allergens or individual fungi (or by the ImmunoCAP ISAC method to fungal allergen components). A digital analytics platform was used to generate primary data. Results. The phenotype of a patient with severe AD and confirmed FS was described. The patient profile is characterized by an extended sensitization spectrum (at least 34 allergen groups) with the most typical combination of pollen, epidermal, and FS. If there is a food allergy, it is of the classic "big eight" nature. Besides exacerbation of the skin disorder, its manifestations include angioedema of life-threatening localization and bronchospasm. Markers of T2 inflammation (high levels of immunoglobulin E and blood eosinophilia) are observed according to the test results, and the T2 endotype of allergy-related abnormalities is typical. Conclusion. Apparently, the presence of FS in patients with AD may exacerbate parenteral sensitization mechanisms, expanding its spectrum, including food allergens. Therefore, distinguishing the phenotype of severe AD with FS needs further detailing with a subsequent adaptation of monitoring and treatment methods of severe AD.